2017
DOI: 10.3390/met7090344
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Effect of Precipitation on the Mechanical Stability of Fine-Grained Austenite in Reversion-Treated 301LN Stainless Steel

Abstract: According to recent investigations, a huge difference exists in the mechanical stability of austenite between the grain-refined structure states obtained in reversion annealing at 800-700 • C or at 900 • C, in a 301LN type austenitic stainless steel. Precipitation of chromium nitride occurring at these lower temperatures has been argued to be the factor reducing the stability. To prove this argument, a fine-grained, very stable austenitic structure was created at 900 • C in 1 s, and subsequently annealed at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…much more stable than the 750-0.1 counterpart at a given CR reduction, in agreement with earlier studies [20,21]. The stability of various reversion-treated structures of 63% cold rolled 301LN steel has been discussed earlier, and the CrN precipitation was proved to be the controlling factor for the difference [30]. However, no previous data are available concerning the influence of the degree of the CR reduction on the stability.…”
Section: Austenite Stabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…much more stable than the 750-0.1 counterpart at a given CR reduction, in agreement with earlier studies [20,21]. The stability of various reversion-treated structures of 63% cold rolled 301LN steel has been discussed earlier, and the CrN precipitation was proved to be the controlling factor for the difference [30]. However, no previous data are available concerning the influence of the degree of the CR reduction on the stability.…”
Section: Austenite Stabilitysupporting
confidence: 88%
“…Hence, the fraction and texture of the medium-sized grains cannot explain the stability difference between these structures created at these different annealing temperatures. The precipitation of CrN in the 750-0.1 structure seems to be the factor which also reduces the austenite stability in the 32CR structures, as confirmed earlier in the instance of the 63CR structures [30]. The mobility of all alloying elements in martensite is high, due to high defect concentration and pipe diffusion, shown to be 45 times higher than in the ferrite phase [35].…”
Section: Martensite Nucleation During Tensile Strainingsupporting
confidence: 61%
“…Moreover, a fast kinetics for the formation of α′-martensite during tension was reported for the UFG samples obtained by ECAP in the 301 grade, which was correlated to the effects of the preexisting microtwins and increasing the dislocation density during the formation of Lüders bands [128]. Furthermore, the chromium nitride precipitation during the formation of UFG structure in the 301LN grade was linked to the reduced stability of the austenite phase in the steel during subsequent deformation [2,166].…”
Section: Grain Sizementioning
confidence: 84%
“…Tomimura et al [39] found that the reversion was diffusional at 652 • C in an 18Cr-9Ni alloy (Ni/Cr = 0.5) in spite of a high heating rate of 300 • C/s. Somani et al [23,80], Kisko et al [27,28,[81][82][83] and Järvenpää et al [84][85][86][87] have used a high heating rate of 200 • C/s in their experiments. They found that in 301LN (Ni/Cr ≈ 0.4), the diffusion-controlled reversion started, depending on prior cold rolling reduction, around 650-700 • C and was completed within few seconds at 750-800 • C. Examples of the influence of cold rolling degree on the reversion kinetics in a 301LN ASS are illustrated in Figure 4, where also the data of Takaki et al [40] for an 18Cr-8.5Ni steel is included.…”
Section: Reversion Mechanismmentioning
confidence: 99%
“…However, the A f temperature for a 301LN ASS has not been clearly reported, and due to the diffusion-controlled reversion, it is dependent on cold rolling reduction and annealing duration, as evident from Figure 4. In that data, about 5%DIM is left after 10 s holding at 700 • C after the 75% reduction, while after the 63% reduction, Järvenpää et al [84] reported 10% of DIM and Rajasekhara [26] 5% after 100 s and 20% after 10 s. Anyhow, in numerous studies, temperatures between 600 and 1000 • C have been used for reversion treatments of 301LN ASS [12,[22][23][24][25][26][84][85][86][87].…”
Section: Temperature Range For Reversionmentioning
confidence: 99%